(untitled) (Revista de História Regional, 2007)
This article analyses the experience of the Ação Popular- AP (Popular Action), one of the most representatives organisations of the Brazilian New Left, in the sixties, in the state of Paraná. In this research, the subject will be investigated by studying the relationship between the national policy of AP and its experience in the regional context.